(x - 3)^2
(x - 3) * (x - 3)
x^2 - 3x
+ -3x + 9
x^2 - 6x + 9
Answer:
x = 0
Step-by-step explanation:
the origin
The Opposite of 3.82 is -3.82. It's like you saying what is the inverse of 3.82.
Answer:
x = 5
Step-by-step explanation:
The difference between consecutive terms will be equal , then
a₂ - a₁ = a₃ - a₂ , that is
x + 9 - (3x - 2) = 2x + 5 - (x + 9) ← distribute parenthesis on both sides
x + 9 - 3x + 2 = 2x + 5 - x - 9 , simplify both sides
- 2x + 11 = x - 4 ( subtract x from both sides )
- 3x + 11 = - 4 ( subtract 11 from both sides )
- 3x = - 15 ( divide both sides by - 3 )
x = 5
Step-by-step explanation:
x increased by 6 is :
= x+6